Patient-Tailored Connectomics Visualization for the Assessment of White Matter Atrophy in Traumatic Brain Injury - Irimia, Andrei; Chambers, Micah C.; Torgerson, Carinna M.; Filippou, Maria; Hovda, David A.; Alger, Jeffry R.; Gerig, Guido; Toga, Arthur W.; Vespa, Paul M.; Kikinis, Ron; Van Horn, John D. (Frontiers in Neurology, 2012)
Available approaches to the investigation of traumatic brain injury (TBI) are frequently hampered, to some extent, by the unsatisfactory abilities of existing methodologies to efficiently define and represent affected structural connectivity and functional mechanisms underlying TBI-related pathology. In this paper, we describe a patient-tailored framework which allows mapping and characterization of TBI-related structural damage to the brain via multimodal neuroimaging and personalized connectomics. Specifically, we introduce a graphically driven approach for the assessment of trauma-related atrophy of white matter (WM) connections between cortical structures, with relevance to the quantification of TBI chronic case evolution. This approach allows one to inform the formulation of graphical neurophysiological and neuropsychological TBI profiles based on the particular structural deficits of the affected patient by relating the findings supplied by our workflow to the existing body of research that focuses on the functional roles of the cortical structures being targeted. Having a graphical means for representing patient TBI status is relevant to the emerging field of personalized medicine as well as to the investigation of human neural atrophy in response to brain trauma.